Therapie des Handekzems - Berthold, Elisa; Weisshaar, Elke (Der Hautarzt, 2019)
The treatment of hand eczema represents a great challenge in the daily clinical practice for dermatologists. There are various forms of local, physical and systemic treatment, such as alitretinoin which is the only registered systemic treatment option for severe chronic hand eczema. In 2017 dupilumab was approved for the treatment of moderate to severe atopic dermatitis and can theoretically also be applied for atopic hand eczema. The first and most important step in treatment is to identify the underlying etiology of the hand eczema with the appropriate diagnostic measures, ranging from skin biopsy to allergy testing including occupational products. An important component of treatment is the basic treatment in the form of consistent and stage-adapted skin care. Treatment of hand eczema should follow a step by step procedure whereby the basic treatment should be maintained and, depending on the etiology and clinical type, should be supplemented by topical, systemic and physical treatment forms, also often used in parallel. Mild to moderate forms of hand eczema are usually treated with the basic treatment, emollients and topical glucocorticoids according to various guidelines. In moderate to severe forms of hand eczema UV phototherapy and systemic treatment should be implemented. This article summarizes the most important treatment modalities based on case reports and series, clinical studies, guidelines and expert recommendations.